Branch Campuses: Extending the Reach of Social Work Education. (3rd April 2019) - Funge, Simon P.; Sullivan, Dana J.; Owens, Larry W.; Harper, Whitney
ABSTRACT: The study explored the characteristics and experiences of branch campus social work education programs and educators in the United States. Eighty-one branch campus social work educators in 26 states completed an online survey. Findings revealed that undergraduate and graduate branch campus social work education was primarily delivered face-to-face to nontraditional students. Half of these programs were recently established, and the majority were expected to grow. However, teaching these students was not necessarily viewed as a shared responsibility. Although some branch campus faculty reported higher workloads and limited connections to parent campus colleagues, faculty generally reported great satisfaction teaching branch campus students. Practical implications are provided.